(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Efforts by successive Nigerian administrations to foster national integration and development have frequently fallen short, leading to a fractured relationship among the federating units. This may be attributed to the lack of a defined national ideology or shared tradition. However, it’s important to note that many nations did not start with full cohesion; instead, national unity often emerges over time through gradual reforms that address the flaws within the national framework. The persistence of narrow nationalist movements in Nigeria, especially since independence, is concerning, as history shows a consistent pattern of agitations. These take forms such as the defense of minority and religious rights or ethnic mobilization, and the Fourth Republic has continued to reflect these complex dynamics. Leaders from one region or ethnic background often encounter dissent from other groups, signaling resistance to perceived marginalization. While protest against ineffective governance is justified, questions remain about the motives behind these movements, as they may not always be driven by a genuine commitment to national unity, making a resolution appear distant. This paper explores the motivations behind these enduring nationalist sentiments to assess their implications for national development. Relying largely on secondary data, as well as accounts from witnesses and historical sources, the study uses a descriptive approach to examine each phenomenon. The instrumentalist theory provides a framework for analysis, suggesting that the prevailing pattern of ethnic-based protest is unlikely to subside soon. Many citizens continue to feel aligned with their ethnic roots, often prioritizing them over national identity. Establishing a sincere democratic system that includes all voices can help alleviate the intensity of these divisions.